A new species of Neoferdina and three new records of sea stars (Echinodermata: Asteroidea) collected from Kumejima Island, southwestern Japan - Kogure, Yoichi; Fujita, Yoshihisa (Zootaxa, 2012)
Sea stars were collected at depths ranging from 91 to 160 m around Kumejima Island situated in the middle of the RyukyuIslands chain in the Western Pacific. Sampling was carried out using a dredge or beam trawl in November 2009, as partof the KUMEJIMA 2009 Expedition. The specimens included an undescribed species of the genus Neoferdina, and threespecies that have never been reported in Japanese waters. Features that characterise this new species, Neoferdina longi-brachia, include: extremely long and narrow arms, no alternating arrangement of large and small superomarginal plates,body surface (except for the marginal plates) completely covered with granules, and an adambulacral armature with 3 furrow spines.